Immigrant language vitality: exploring the language practices of some Nigerian immigrants in Cape Town - Umana, Beauty (School of African and GenderStuds, Anth and Ling, 2023)
This study draws on the conceptual framework of language maintenance and shift to examine the phenomenon of West African migration to post-apartheid South Africa. The study aims to determine how immigrants negotiate language and cultural differences, how attempts to integrate into their new society shape or reshape their identities, the consequences of this attempt at integration on their home languages and ultimately, their placement in their new society. It follows a qualitative research methodological approach for data collection where participants' language use and language choices are observed. Unstructured interviews and participant observation were utilised as tools for data collection. The data was analysed using thematic analysis to identify the themes and patterns that emerged from the qualitative data collected. Following an interpretive paradigm, the study was done to record how space, mobility, and anti-immigrant sentiments impact the language choices of immigrants in Cape Town, South Africa. All South African cities are highly multilingual and multicultural including Cape Town. Although South Africa has eleven official languages (now 12 with the recent addition of sign language), many other languages have made their way into the country because of the flow of immigrants from already highly multilingual and multicultural African countries. Migration studies have shown that Africans migrate with complex, fluid and multi-layered linguistic repertoires which develop into an even more complex one in their new society because of their multilingual backgrounds. Although researchers (Vigouroux, 2008; Wankah, 2009; Mbong, 2008; Orman, 2012; Nchang, 2018) have done some work on West African migration to South Africa, these studies have not extensively documented the impact of Nigerian migrants' language practices or choices on the vitality of their heritage languages in Cape Town. The present study, therefore, focuses on some Nigerian immigrants in Cape Town by examining the effect of space and identity negotiation in the diaspora on their home languages. It raises the question: what is the fate of immigrant heritage languages such as Yoruba and Nigerian Pidgin English in the diaspora in terms of language maintenance and shift? To the researcher's current knowledge, there is no study on language maintenance and shift with regard to Nigerian Pidgin and Yoruba in Cape Town. Therefore, there is no evidence suggesting the maintenance or shift of these languages. Based on this, the current research set out to investigate the vitality of said languages in Cape Town. In addition, it is important to monitor and document immigrants' languages in the diaspora. Research such as this potentially builds on existing works and expands scholarly knowledge in the field of language maintenance and shift as it relates to migrants' heritage languages. This dissertation explores the vitality of Nigerian immigrants' languages, Nigerian Pidgin and Yoruba, within the context of Cape Town. This is done through an exploration of the linguistic practices of selected Nigerian immigrants residing in some areas of Cape Town, South Africa, focusing on the impact of their language use patterns on the maintenance of their home languages or shift from them. The focus on Yoruba and Pidgin reflects the two main languages of Nigeria today; these are languages that I can monitor in migration. Furthermore, while Yoruba has “ethnic” overtones, Pidgin is more widely construed as “Nigerian”, hence it is necessary to study both together. The analysis of data indicates that immigrants' social positioning as both outsiders and insiders in their new society presents certain challenges to the vitality of their heritage languages. On the one hand, they grapple with the desire to maintain their identities as Nigerians but on the other, they risk exclusion and discrimination which can sometimes be life-threatening should they maintain their cultural affiliations and heritage languages. This places them in a difficult position. This study illuminates some of the challenges immigrants face as they negotiate their place in their new societies.